PENGARUH HANDOUT FISIKA MULTIMEDIA INTERAKTIF BERBASIS DISCOVERY LEARNING BERBANTUAN GAMES TERHADAP CRITICAL THINKING SKILLS PESERTA DIDIK KELAS X SMAN 3 PADANG - Muhammad Khairul Jawad; Djusmaini Djamas; Gusnedi Gusnedi (PILLAR OF PHYSICS EDUCATION, 2017)
This research originated from the fact that learning in school is still not involve students learn actively, learning that takes place is still centered on the teacher, the use of teaching materials that do not attract resulting in low yields physics learning and critical thinking skills of learners. This research aims to investigate the influence of handout of physics interactive multimedia based discovery learning aided games to the critical thinking skills of students grade X SMAN 3 Padang. The hypothesis of this research is there are a meaningful impact handout of physics interactive multimedia based discovery learning aided games to the critical thinking skills of students grade X SMAN 3 Padang.To achieve the goal of the research conducted quasi-experimental research design with randomized control group only design. The research population was all students of class X SMAN 3 Padang enrolled in the academic year 2016/2017 and sampling using purposive sampling and class X chosen as an experimental class X MIA 1 and  class X MIA 2 as the control class. The research instrument in the aspect of knowledge is the achievement test.Based on the analysis of data obtained the product moment correlation analysis shows that the interactive multimedia teaching materials physics game aided contributing to critical thinking skills of students by 28%. The conclusion from this research is there a meaningful impact handout of physics interactive multimedia based discovery learning aided games to the critical thinking skills of students grade X SMAN 3 Padang